PERISTILAHAN ADAT PERNIKAHAN PADA MASYARAKAT MADURA DI WAJOK HILIR, KABUPATEN MEMPAWAH - Suhardi, Suhardi; Muzammil, Ahmad Rabi’ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract The study of the Madurese Traditional Marriage Terminology in Mempawah in WajokHilir Village has three traditional processions that must be carried out by the bride and groom and their families. First, the pre-wedding procession which consists of five traditional processes that must be carried out, namely; (1) ngangane, (2) arabe fence, (3) nyabe' snack, (4) teketpetton, and (5) nyedektemo. After carrying out the pre-wedding rituals or traditional traditions, the second procession is followed by a wedding procession. In the wedding procession, there are four traditional processions that the bride and groom must undergo, namely; (1) arepbe, (2) bereskoneng, (3) contract, and (4) delivery of the weakest delivery. Then the third or final procession is the post-wedding procession. In the postwedding procession, the bride and groom are required to carry out the traditional cenglanceng ritual, the ritual is a closing ritual. In the cenglanceng ritual, the bride and groom carry out a slametan procession or salvation for the marriage that has been carried out and hope that the marriage can get safety and happiness in building a household. Keywords: Terminology, wedding, Madura community,